A weighted throttled load balancing approach for virtual machines in cloud environment. (2015) - Hussein, Walugembe; Peng, Tao; Wang, Guojun
In a cloud environment, load balancing techniques play a vital role in reducing costs associated with file management systems and maximise availability of resources by reducing the amount of downtime that affects the system during outages. Virtualisation technology provides an effective solution to the management of dynamic web-based resources and this prompted us to propose a virtual machine load balancing algorithm. In this paper, we propose a weighted throttled load balancing algorithm, a modification of throttled load balancing algorithm by assigning a weight to each virtual machine (VM). For throttled load balancing algorithm, virtual machines (VMs) are either busy or available and if there is no VM available to serve a request, the request is queued. In our proposed algorithm a request is not queued instead it is assigned a busy VM that has a higher weight in comparison to other VMs. The proposed approach improves system availability through minimising latency, and reduces processing time through proper allocation of requests to the most powerful VM available. The algorithm is implemented using CloudSim simulator and the experimental results achieve better response time and processing time.